Python : Expert Machine Learning Systems and Intelligent Agents Using Python. - Bonaccorso, Giuseppe (Packt Publishing Ltd, 2018)
This Learning Path is your complete guide to quickly getting to grips with popular machine learning algorithms. You'll be introduced to the most widely used algorithms in supervised, unsupervised, and semi-supervised machine learning, and learn how to use them in the best possible manner. Ranging from Bayesian models to the MCMC algorithm to ...